Designing a Child-Centric Android Mathematics Application: A Technological Approach to Early Childhood Cognitive Development - Juliana; Siti Khotijah; Dewi Driyani (International Journal of Progressive Mathematics Education, 2026)
Purpose: This study aims to develop a specialized Android-based mathematics learning application to address specific cognitive barriers in grasping fundamental number concepts and basic arithmetic among preschool children at TPQ Al Falah, Depok. Design/methodology/approach: Adopting the Waterfall development model—comprising requirement analysis, system design, coding, and rigorous testing—the study engaged pupils aged 4–6. Research instruments involved qualitative observations, semi-structured interviews, and black-box testing focusing on interactive quiz functionalities to evaluate pedagogical efficacy. Findings: Results indicate that the application effectively facilitates the mastery of numbers 1–10 and basic arithmetic operations. The strategic integration of synchronized audio-visual stimulation and gamification elements significantly enhanced student attention spans and intrinsic learning motivation. Practical implications: The application serves as a robust autonomous tool for educators and parents, facilitating a seamless transition from conventional instructional methods to interactive digital pedagogies. Originality/value: This study contributes to TPACK literature by uniquely synthesizing reversible reasoning and the "productive struggle" framework within digital learning media specifically tailored for early childhood education.   Purpose: Penelitian ini bertujuan untuk mengembangkan aplikasi pembelajaran matematika berbasis Android yang dirancang khusus guna mengatasi hambatan kognitif spesifik dalam memahami konsep angka dasar dan aritmetika awal pada anak usia prasekolah di TPQ Al Falah, Depok. Design/methodology/approach: Dengan mengadopsi model pengembangan Waterfall yang mencakup tahapan analisis kebutuhan, perancangan sistem, pengkodean, dan pengujian ketat, studi ini melibatkan siswa berusia 4–6 tahun sebagai subjek utama. Instrumen penelitian meliputi observasi kualitatif, wawancara semitersetruktur, serta pengujian black-box yang berfokus pada fungsionalitas kuis interaktif untuk mengevaluasi efikasi pedagogis sistem. Findings: Temuan menunjukkan bahwa aplikasi ini secara efektif memfasilitasi penguasaan angka 1–10 dan operasi hitung dasar. Integrasi strategis antara stimulasi audio-visual yang sinkron dengan elemen gamifikasi terbukti meningkatkan rentang perhatian dan motivasi belajar intrinsik siswa secara signifikan. Practical implications: Aplikasi ini berfungsi sebagai instrumen otonom yang tangguh bagi pendidik dan orang tua, memungkinkan transisi yang mulus dari metode instruksional konvensional ke arah pedagogi digital yang interaktif. Originality/value: Studi ini memberikan kontribusi baru pada literatur TPACK dengan mensisntesis penalaran reversibel dan kerangka kerja "tantangan produktif" dalam media pembelajaran digital yang disesuaikan khusus untuk pendidikan anak usia dini.